2009
DOI: 10.1016/j.bcp.2009.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Statins inhibit Akt/PKB signaling via P2X7 receptor in pancreatic cancer cells

Abstract: To cite this version:Oras Mistafa, Ulla Stenius. Statins inhibit Akt/PKB signaling via P2X7 receptor in pancreatic cancer cells. Biochemical Pharmacology, Elsevier, 2009, 78 (9) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 38 publications
7
56
0
Order By: Relevance
“…We also find that the downstream signaling of Akt is attenuated, and that the selection process resulted in an apparently stable cell phenotype exhibiting a reduced or absent nuclear pAkt response to insulin. These alterations confirm our previous results indicating that statins target the P2X7-Akt axis in cultured cells (13)(14)(15). Our present results also suggest that this axis is an important cell signaling pathway that might be critical for statin toxicity and that can modify insulin signaling.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We also find that the downstream signaling of Akt is attenuated, and that the selection process resulted in an apparently stable cell phenotype exhibiting a reduced or absent nuclear pAkt response to insulin. These alterations confirm our previous results indicating that statins target the P2X7-Akt axis in cultured cells (13)(14)(15). Our present results also suggest that this axis is an important cell signaling pathway that might be critical for statin toxicity and that can modify insulin signaling.…”
Section: Discussionsupporting
confidence: 92%
“…Different types of statins have been reported to decrease the levels of phosphorylated Akt in several cell lines, and our group has shown that pravastatin, simvastatin and atorvastatin lower the insulininduced nuclear pAkt accumulation without affecting the total Akt levels in A549 cells (15). This effect is mediated by P2X7, and is associated with altered phosphorylations of downstream targets of pAkt, including GSK3β and cyclin D1 (13,14).…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations